« À bas les Anglais ! » - Fabrice Bensimon (Diasporas: Circulations, Migrations, Histoire)
Under the July monarchy (1830-1848), British workers who had gone to France to work in textile, iron, and railway building were sometimes targeted by collective mobilisations. These became more numerous in the weeks following the February 1848 fall of the monarchy. Scottish cotton workers in Eure, Scottish and Irish linen workers in Petit-Quevilly (Seine-Inférieure) were targeted and had to leave. In Calais, English lace makers also reported a xenophobic outburst. This article addresses the rationale of these mobilisations, at a time when the Republic had just been proclaimed and celebrated fraternity.